Optimizing breastfeeding succes post-cesarean: A quasi-experimental study on biological nurturing baby-led feeding video intervention - Rialike Burhan; Desi Widiyanti; Elly Wahyuni; Novia Nuraini; Lia Artika Sari (Alma Ata University Press, 2026)
Background: The coverage of exclusive breastfeeding in Bengkulu Province remains low, reaching 67.08% and even declining to 52.9% in 2022, which is below the national average of 71.58%. Mothers who undergo cesarean section (CS) deliveries are more likely to experience early breastfeeding failure. Approximately 68% of post-CS mothers face difficulties in caring for their newborns and moving in and out of bed due to post-surgical pain. Objectives: This study aims to evaluate the effect of an educational video on Biologic Nurturing Baby-Led Feeding on the knowledge, attitudes, and breastfeeding success of post-cesarean section mothers in Bengkulu City. Methods: This study employed a quasi-experimental design using a pre-post test group approach. The research was conducted in several three.Type C hospitals in Bengkulu City from January to November 2024. A total of 60 participants were divided into two groups: the intervention group, which received education through video media, and the control group, which used a pocket book as the educational tool. The data analysis included univariate analysis, bivariate analysis using the Independent Sample T-Test, and multivariate analysis using MANCOVA. Results: Statistical analysis revealed that the use of Biologic Nurturing Baby-Led Feeding educational video had a significant impact on mothers’ knowledge, attitudes, and breastfeeding success (p-value = 0.05). Effect Size : knowledge : 0.555, attitudes: 0,662 and breastfeeding success : 0.735 Conclusions: Health education can improve mothers' knowledge, attitudes, and breastfeeding success. However, the use of the Biologic Nurturing Baby-Led Feeding educational video proved to be more effective and was preferred by the respondents.